Islam and Medical Science: Evidence from Malaysian and Indonesian Fatāwā, 1960-1995 - Hooker, M.B. (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1997)
The purpose of this paperis to illustrate some of the dilemmas in which Islam finds itself with respect to advamces in modern medical science. This is of course a very large subject and all I can do here is to take a very small sample of problems as expressed in fatawa (legal rulings-see futher below) over the past thirty years. Coincidentally, these are also the years which have seen tremendous advances in medicine and the ways in which we can now treat (or mistreat?) the human body.DOI: 10.15408/sdi.v4i4.764